Copper-Catalyzed Oxidative ipso-Cyclization of N-(p-Methoxyaryl)propiolamides with Disulfides and Water Leading to 3-(Arylthio)-1-azaspiro[4.5]deca-3,6,9-triene-2,8-diones - Qian, Peng-Cheng; Liu, Yu; Song, Ren-Jie; Xiang, Jian-Nan; Li, Jin-Heng (Synlett, 2015)
A new copper-catalyzed oxidative ipso-cyclization of N-(p-methoxyaryl)propiolamides with disulfides for the synthesis of 3-(arylthio)-1-azaspiro[4.5]deca-3,6,9-triene-2,8-diones has been developed. This method proceeds via sequential oxidative C–S bond formation, ipso-cyclization, and dearomatization and provides a new facile oxidative strategy to assemble the target products using an inexpensive catalytic system comprising copper(II) chloride and molecular oxygen.
Keywords: copper; cyclization; N-(p-methoxyaryl)propiolamides; disulfides; 3-(arylthio)-1-azaspiro[4.5]deca-3,6,9-triene-2,8-diones